Thermal performance of Rice Husk Ash mixed mortar in concrete and masonry buildings - Selvaranjan, Kajanan; Gamage, J.C.P.H.; De Silva, G.I.P.; Attanayaka, Vajira (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
Rice Husk (RH) is an agricultural waste which is produced in huge amounts from the milling process of paddy rice. Rice Husk Ash (RHA) is a by-product material obtained from the combustion of rice husk. The amorphous silica-rich RHA (84-90 wt%) has a wide range of applications. This research focused on the possibility of utilizing RHA in the process of developing a mortar with low thermal conductivity to enhance the thermal comfort in concrete and masonry buildings. The thermal conductivity of mortar was determined by Lee’s Disc method, and the results were compared to the data for conventional mortar as well as commercial thermal insulation materials. The results indicate a significant reduction in thermal conductivity in the mortar developed with RHA